Análise da ação analgésica da Borreria Verticillata (L.) G. Mey. em modelo experimental de osteoartrite em rato - RODRIGUES, Marineide Sodré (2019)
Osteoarthritis (OA) is the most common form of joint disease by changing the quality of life, being the most frequent cause of musculoskeletal pain for the activities of daily living and labor activity in Brazil and in the world, becoming a health problem with implications socioeconomic. OA has no cure and has a direct impact on the economy as a result of high public spending with medicines and hospital care. The aim of this study was to evaluate the analgesic effect and extract raw to evaluate therapeutic (EHBv) and ethyl acetate fraction (FAc) of Borreria verticillata (l.) g. Mey. (BV) in experimental model of OA in the knees of rats. The animals were divided into seven groups with 6 animals each, totaling 42 animals. Was induced OA with a single intra-articular injection of sodium Monoiodoacetato (MIA) in his right knee in six groups (Salina, Melox, EHBv, FAc 5 mg, FAc 2, 5 mg, ursolic Acid (AU) and the 7th Group (no OA) was not induced. From the 3rd day after induction, the animals were treated until the 28th day, by gavage (mouth) with extract and fractions of BV in the following EHBv doses 500 mg/kg/day, 5 mg/kg/day FAc, FAc 2, 5 mg/kg/day and AU 10 mg/Kg/day and Meloxicam 7, 5 mg/kg/day. Clinical behavioral assessment used the parameters of: motor activity/forced ambulation, quantification of spontaneous pain and evaluation of mechanical allodynia; analysis of incapacitância/weight distribution on the hind legs and mechanical hyperalgesia. The pharmacological study significantly mitigated the behavioral manifestations of pain in animals treated with the extract and its fractions compared with the saline Group (0, 1 ml/Kg) suggesting an analgesic action of BV. The species Borreria verticillata (l.) g. Mey. for the treatment of osteoarthritis, reveals himself to be a promising compound for the development of drugs used for analgesia, can be useful in the treatment of different types of pains and as adjuvants for conventional medicines.